2021
DOI: 10.3390/ijerph18147239
|View full text |Cite
|
Sign up to set email alerts
|

A Multicentre, Randomised, Controlled Trial of a Combined Clinical Treatment for First-Episode Psychosis

Abstract: Introduction: There is evidence that early intervention contributes to improving the prognosis and course of first-episode psychosis (FEP). However, further randomised treatment clinical trials are needed. Objectives: The aim of this study was to compare the efficacy of a combined clinical treatment involving Cognitive Behavioural Therapy (CBT) as an adjunctive to treatment-as-usual (TAU) (CBT+TAU) versus TAU alone for FEP. Patients and methods: In this multicentre, single-blind, randomised controlled trial, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Since cannabis has a significant role in the prognosis of FEP patients and given that the deleterious effect of cannabis could be reversed with the decrease or cessation of consumption, there is a need for early intervention for cannabis cessation after the onset of FEP. Although CBT has previously proven to be a useful therapeutic approach to treat and improve clinical and functional outcomes in FEP [ 62 ], to date no specific therapies had been found that have been shown to be effective for FEP cannabis users. This integrated psychological CBT intervention has been shown to be effective both in cannabis cessation use and in improving clinical and functional outcomes of FEP cannabis users, following the paradigm of precision psychotherapy [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since cannabis has a significant role in the prognosis of FEP patients and given that the deleterious effect of cannabis could be reversed with the decrease or cessation of consumption, there is a need for early intervention for cannabis cessation after the onset of FEP. Although CBT has previously proven to be a useful therapeutic approach to treat and improve clinical and functional outcomes in FEP [ 62 ], to date no specific therapies had been found that have been shown to be effective for FEP cannabis users. This integrated psychological CBT intervention has been shown to be effective both in cannabis cessation use and in improving clinical and functional outcomes of FEP cannabis users, following the paradigm of precision psychotherapy [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, teams dedicated to specific interventions in first-episode psychosis have proliferated, showing more promising results when compared to those obtained in standard services [ 1 , 15 , 19 ]. These teams promote recovery and a productive life.…”
Section: Introductionmentioning
confidence: 99%
“…These teams promote recovery and a productive life. They offer appropriate interventions aimed at ameliorating clinical outcomes, such as the impact of symptoms, improving functioning, and reducing relapse with a view to recovery as early as possible [ 19 , 20 , 21 ]. Recovery encompasses the issues of clinical recovery and personal recovery.…”
Section: Introductionmentioning
confidence: 99%